Effect of transglutaminase on gel properties of surimi and precocious Chinese mitten crab (Eriocheir sinensis) meat. (January 2020) - Liang, Feng; Lin, Lin; He, Tianhai; Zhou, Xianhan; Jiang, Shaotong; Lu, Jianfeng
Abstract: We examined the effect of transglutaminase (TG) on the gel properties of silver carp ( Hypophthalmichthys molitrix ) surimi in combination with different proportions (0–30%) of precocious Chinese mitten crab ( Eriocheir sinensis ) meat. Our results show that in the presence and absence of TG, the protein breaking force and deformation reduced significantly ( P  < 0.05) as the proportion of crabmeat increased. However, following incorporation of TG (0.4%), the breaking force, deformation, and unfrozen water (Wu ) content were markedly increased ( P  < 0.05), most notably when crabmeat was absent. Moreover, with increasing proportions of crabmeat the a* (redness/greenness) and b* (yellowness/blueness) of the product increased significantly ( P  < 0.05), while L* (lightness) and whiteness decreased. Moreover, noticeable differences were observed between groups that contained TG compared to those that did not. Further, the concentrations of myosin heavy chain (MHC) was found to increase in the presence of crabmeat, while the addition of TG served to catalyze the formation of non-disulfide covalent bonds, thereby causing less MHC to be detected. Nevertheless, no significant change in the secondary structure ( P  > 0.05) of the proteins was noted, yet all gels that contained TG exhibited a more compact and regular protein network compared to those without TG. These results suggest that the addition of crabmeat may negatively impact gel formation by surimi, while the incorporation of TG may serve to improve mixed gel properties. Graphical abstract: Image 1 Highlights: More intense color and higher content of Wu occurred after the incorporation of TG. Crabmeat interfered with mechanical properties and microstructure of mixed gel. No markedly change occurred in secondary structure in presence of TG and crabmeat. TG could improve surimi/crabmeat mixed gel properties efficiently. The improvement of TG is limited at high levels of crabmeat addition.